Inflation and stock market development in Namibia: Evidence from co-integration and error correction modelling (Journal for Studies in Humanities and Social Sciences, 2015)
The current study looks at the relationship between infl ation and stock market development in Namibia using modern time series econometric techniques that of co-integration and error correction modelling. The main results in this paper indicate that real gross domestic product promote stock market development in Namibia. More particularly, changes in gross domestic product impacts positively on market capitalization and the value of domestic shares traded. The results also indicate that there is a relationship between infl ation and market capitalization and value of domestic shares traded. However, this relationship is insignifi cant. The foregoing implies that Namibia should place emphasis on the policies that promote gross domestic product, because this is benefi cial for the development of the stock market. Although the relationship between stock market development indicators and infl ation is insignifi cant, there is a need for the country to continue pursuing monetary policy that ensures a low and stable infl ation. This is important because low and stable infl ation encourages stock market activities. In other words, it is important for monetary policy to remain fi rm and conducive in future for the betterment of sound and sustainable development of the stock market and general economic activities.